Internalization of the Concept of Character Education According to Ki Hadjar Dewantara and Its Implementation in Kurima State Middle School - Mellolona Pasembang; Sensius Amon Karlau; Rasinus Rasinus (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Character education is an education system that aims to instill certain character values in students, in which there are components of knowledge, awareness or willingness and actions to carry out these values. The Importance of application character education to students at Kurima State Junior high school is because many of them showed poor behavior and harsh character. The main purpose of this research is to find out Ki Hajar Dewantara’s character education and internalize these concept at Kurima State Junior High School. Results of this research showed that Ki Hadjar Dewantara seeks to instill national education foundation based on principles of Indonesia, one of that principle is Culture principle. Ki Hadjar Dewantara culture principle said that culture must be explored and developed through character education. And that culture principle implemented through instill character values in school culture, when school provision facilities support school program and school habituation in daily life at school. School program’s must be designed to form students character by design the right activities at school environment and student get used to character values that designed by school.